Media’s Influence on Female Relational Aggression and Its Implications for Schools - Virtanen nee Redden, Crystal (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
The author of this paper explores the media’s role in the normalization of relational aggression of females and the implications this can have in schools. It is important that those who teach, support, and develop curricula for students be aware of the media’s role in the use, and the effects, of indirect aggression and have information on how to approach reducing the effect that the media can have. Trends and effects of relational aggression are highlighted. The media’s role in normalizing relational aggression in females is explored, with a specific look at Disney’s films as well as the effect the media’s influence can have on youth and families. This paper will consider current tactics employed by schools and the challenges schools face. It will conclude with a look at future ideas for combating the normalization of relational aggression in the media. Keywords: relational aggression, females, media, Walt Disney, education